The project-level Women's Empowerment in Agriculture Index: How we are developing a new index - Martinez, Elena (International Food Policy Research Institute, 2018)
Presented by Elena Martinez (IFPRI/A4NH), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.